ОПРЕДЕЛЕНИЕ СОДЕРЖАНИЯ ПЕРВИЧНОГО ГЕЛИЯ ПО РЕКОМБИНАЦИОННЫМ РАДИОЛИНИЯМ - Цивилев, А. П.; Парфенов, С. (Одеські астрономічні публікації, 2011)
The determination of the Primordial helium abundance (Yp) by recombination radio lines (RRL) is made, and the new results over the paper [1] are presented. The results of new RRL H,He observations in source W51 at 8 and 13 mm are presented. Then new analysis of H and He RRL observation data on sixth galactic HII regions, obtained at different time, is made. The Yp = 25.85((±0.68)% is obtained. This value allows to exist of unknown light particles at the Big Ban beginning, i.e. may assume a deviation from Standard Cosmological model.